2021
DOI: 10.3390/s21082841
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Context, Correlation Filter and Measurement Estimation Collaboration Based Visual Object Tracking

Abstract: Despite eminent progress in recent years, various challenges associated with object tracking algorithms such as scale variations, partial or full occlusions, background clutters, illumination variations are still required to be resolved with improved estimation for real-time applications. This paper proposes a robust and fast algorithm for object tracking based on spatio-temporal context (STC). A pyramid representation-based scale correlation filter is incorporated to overcome the STC’s inability on the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recent literature shows that researchers are continuously trying to handle tracking failure and redetecting the target after failure. Notable articles relevant to tracking failure detection and avoidance occlusion handling are presented in [5,24] and [25,26], respectively. Discriminative correlation filter trackers also suffer from boundary effects.…”
Section: Related Workmentioning
confidence: 99%
“…Recent literature shows that researchers are continuously trying to handle tracking failure and redetecting the target after failure. Notable articles relevant to tracking failure detection and avoidance occlusion handling are presented in [5,24] and [25,26], respectively. Discriminative correlation filter trackers also suffer from boundary effects.…”
Section: Related Workmentioning
confidence: 99%
“…To handle occlusion and deformation robustly, several strategies [40][41][42][43][44] have been used. In deep learning methods, data collection and annotation is the most straightforward way, while it seems impossible to collect data covering all potential occlusion and deformation, even for large-scale datasets.…”
Section: Related Work 21 Occlusion and Deformation Handling In Visual...mentioning
confidence: 99%
“…A Kalman filter is used in various tracking algorithms for occlusion handling [45][46][47][48][49]. Kaur et al [50] suggested a real-time tracking approach using a fractional-gain Kalman filter for nonlinear systems.…”
Section: Related Workmentioning
confidence: 99%